Inducible repair of O-alkylated DNA pyrimidines in Escherichia coli. - McCarthy, T V (1984)
The three miscoding alkylated pyrimidines O2-methylcytosine, O2-methylthymine and O4-methylthymine are specifically recognized by Escherichia coli DNA repair enzymes. The activities are induced as part of the adaptive response to alkylating agents. O2-Methylcytosine and O2-methylthymine are removed by a DNA glycosylase, the alkA+ gene product, which also acts on N3-methylated purines. O4-Methylthymine is repaired by a methyltransferase, previously known to correct O6-methylguanine by transfer of the methyl group to one of its own cysteine residues. It is proposed that certain common structural features of the various methylated bases allow each of the two inducible repair enzymes to recognize and remove several different kinds of lesions from alkylated DNA.